RHETORICAL STYLE AND FIGURATIVE STYLE USED BY JOKOWI’S SPEECH IN PLENARY SESSION IMF-WORLD BANK ANNUAL MEETINGS 2018 - Merlin Helentina Napitupulu (Jurnal Mantik Penusa, 2018)
The ways individual’s speech conveys varieties aspects, not only their original and social dialects but also according to the context. The distinctive manner in which people express themselves in a particular situation referred to as style. The purpose of this study was to describe the language style used by Jokowi’s Speech in Plenary Session IMF-WORLD Bank Meetings 2018 based on Keraf’s  theory which classifies language style: rhetorical style and figurative style. The president of Indonesia, Jokowi, is a humble, creative and he delivers his speech simply and briefly. This research was descriptive qualitative research based on speech delivered by Jokowi in Plenary Session IMF-WORLD Bank Annual Meetings 2018. There are rhetorical style and figurative style used by Jokowi’s speech.  Keywords: Rhetorical style, figurative style, speech